PSX-25 Effect of total replacing inorganic trace minerals with low dose organic trace minerals on reproductive performance, mineral status and fecal mineral excretion of sows. (7th December 2018) - Ma, L; Hou, C; He, J; Qiu, J; Liu, B; Lin, G; Xue, Y; Koontz, A; Yu, D
Abstract: This study evaluated total replacement of inorganic trace minerals (ITM) with low-dose organic trace minerals (OTM) on reproductive performance, mineral status, milk immunoglobulin content, and fecal mineral excretion of gestating and lactating sows. Eighty crossbred sows (Duroc x Landrace x Large White, parity 2–6) with similar body weight (BW, 202 ± 8 kg) and breeding date were randomly allocated to 2 treatments in 40 replicates to receive 1 of two diets from breeding through 21 days postpartum for 135 days. The two treatments were as follows: ITM: a basal diet + inorganic Fe, Cu, Mn, and Zn at 90, 15, 25 and 90 mg/kg, respectively; OTM: a basal diet + organic Fe, Cu, Mn and Zn at 72, 12, 20, and 72 mg/kg, respectively (equivalent to 80% of ITM; Bioplex®, Alltech Inc, Nicholasville, KY). Data were analyzed by T-test (SPSS 22.0) with mean ± SD. Compared with ITM, OTM-fed sows had more (n = 0.64) piglets with birth weight > 1kg and a higher litter weaning weight (9.36 kg) (P < 0.05). OTM feeding raised Fe and Cu contents in milk (P < 0.05) and Zn content in colostrum (P = 0.09), while trace mineral contents in the hair of sows during gestation and lactation did not differ (P > 0.05). No differences for IgM, IgG, or IgA contents in colostrum and milk were observed between the two treatments. OTM dramatically decreased fecal Fe, Cu, Mn and Zn contents in gestating sows (P < 0.01) and Fe, Mn and Zn excretion in the manure of lactating sows (P < 0.01) in comparison to ITM. The results indicate that use of dietary organic Bioplex Fe, Cu, Mn, and Zn at 80% of commercially recommended levels improved reproductive performance and milk Fe and Zn concentrations of sows, while significantly reducing fecal mineral excretion. Key Words: